Impact of Emotional Arousal on Sense of Agency and Time Perception - Rehmat, Yash (Thapar Institute of Engineering and Technology, 2025)
Previous studies on the sense of agency and temporal processing have primarily examined how intended action affects temporal processing, such as the perception of time intervals between actions and outcomes. However, it remains largely unexplored how specific stimulus features, such as color and arousal, might modulate both the sense of agency and time perception. Understanding this interaction could provide important insights into how non-temporal sensory attributes influence our perception of time, particularly in the context of voluntary and involuntary actions. In the present thesis, we aim to investigate how stimulus-related features—specifically color-induced arousal—affect individuals’ sense of agency and their estimation of time intervals. To explore this, we conducted two experiments in which participants were asked to estimate the duration between a keypress and the onset of an auditory stimulus. During the inter-stimulus interval (ISI)—the period between the keypress and the sound—a colored screen was presented. We used two colors to induce different levels of arousal: red (high arousal) and gray (low arousal). Participants were then asked to judge the duration of the ISI. In Experiment 1, participants made the keypress themselves to trigger the sound stimulus, reflecting a condition with high sense of agency. In Experiment 2, the experimenter made the keypress on behalf of the participant, simulating a condition with reduced agency. In both experiments, participants were required to estimate the duration of the ISI during which the colored stimulus was presented. The results from both experiments indicated that color had a significant effect on time estimation. Specifically, intervals presented with the red color were perceived as longer compared to those with the gray color. Moreover, a significant difference in duration estimates was observed between the two experimental conditions. When participants actively initiated the action (Experiment 1), their time estimates differed significantly from those in the passive condition (Experiment 2). This suggests that intended actions, associated with a stronger sense of agency, modulate time perception differently than unintended or passive actions. These findings highlight the complex interplay between sensory features, agency, and temporal perception and contribute to a broader understanding of how action and perception are intertwined.
Keywords: Time Perception; Arousal; Sense of Agency; Intentional Binding; Sensory Processes